City Planning. A Very Short Introduction. - Abbott, Carl (Oxford University Press, 2020)
Carl Abbott provides a broad international overview of progress in city planning over the last century and examines the intersectional nature of urban design and development.
Keywords: Stadtplanung; Planungsgeschichte; Planungsansatz; Planungsaufgabe; Querschnittsaufgabe; Stadtentwicklung; Planungsinhalt; Einführung